2014
DOI: 10.14245/kjs.2014.11.4.221
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Alendronate and Endplate Degeneration to Single Level Posterior Lumbar Spinal Interbody Fusion

Abstract: ObjectiveUsing alendronate after spinal fusion is a controversial issue due to the inhibition of osteoclast mediated bone resorption. In addition, there are an increasing number of reports that the endplate degeneration influences the lumbar spinal fusion. The object of this retrospective controlled study was to evaluate how the endplate degeneration and the bisphosphonate medication influence the spinal fusion through radiographic evaluation.MethodsIn this study, 44 patients who underwent single-level posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Kim et al also studied the effect of alendronate on 44 patients undergoing single-level lumbar interbody fusion and instrumentation in 2014 and found different results. 17 They found a nonstatistically significant difference in the fusion rates as assessed by plain radiographs. The patients in the alendronate group had a fusion rate of 66.7% and the control group had 73.9%, with an overall higher rate of patients with end plate degeneration in the alendronate group.…”
Section: Resultsmentioning
confidence: 95%
“…Kim et al also studied the effect of alendronate on 44 patients undergoing single-level lumbar interbody fusion and instrumentation in 2014 and found different results. 17 They found a nonstatistically significant difference in the fusion rates as assessed by plain radiographs. The patients in the alendronate group had a fusion rate of 66.7% and the control group had 73.9%, with an overall higher rate of patients with end plate degeneration in the alendronate group.…”
Section: Resultsmentioning
confidence: 95%
“…Dosing was given starting two months before surgery and continued for ten months after surgery [ 11 ], in 3-month cycles [ 15 ], beginning two months before surgery and continued for eight months after surgery [ 12 ], and the final study was given in short duration (less than six months) or long duration (greater than six months) groups [ 13 ]. Demographic information is listed in Table 2 [ 8 9 10 11 12 13 14 15 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…At one year postoperatively, fusion was observed in 95% (18/19) of the alendronate group and 65% (11/17) of the control group ( p =0.025). There were also higher rates of cage subsidence in the control group (5 patients) versus the alendronate group (1 patient), however this was not statistically significant ( Table 3 ) [ 8 9 10 11 12 13 14 15 16 ].…”
Section: Resultsmentioning
confidence: 99%
“… 11 , 14 , 16 In a retrospective controlled study, Kim et al found that endplate degeneration decreases the fusion rate and that alendronate does not influence the fusion process. 12 …”
Section: Discussionmentioning
confidence: 99%